Learning, Philosophy, and African Citizenship - Holma, Katariina; Kontinen, Tiina (Springer Nature, 2022)
The book addresses the compelling questions concerning the ideals of African citizenship, the processes of learning to fulfill these ideals, and possibilities of education in fostering citizenship. Rather than advocating for one particular framework, the authors demonstrate the continuously contested nature of the concept of citizenship as both theoretically discussed by philosophers and practically experienced in daily lives. The monograph combines, in an unconventional way, selected philosophical accounts and everyday experiences from certain locations in Tanzania and Uganda. It provides contributions from philosophical ideas drawing on scholars such as Chantal Mouffe, Rosi Braidotti, Theodor Adorno and Étienne Balibar on one hand, and the conceptions articulated by groups of inhabitants of rural and urban settings in Africa, on the other hand. Therefore, the book offers fresh readings under the lenses of citizenship and learning. This is an open access book.